-4(3a-1)=

Simple and best practice solution for -4(3a-1)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(3a-1)= equation:


Simplifying
-4(3a + -1) = 0

Reorder the terms:
-4(-1 + 3a) = 0
(-1 * -4 + 3a * -4) = 0
(4 + -12a) = 0

Solving
4 + -12a = 0

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-4' to each side of the equation.
4 + -4 + -12a = 0 + -4

Combine like terms: 4 + -4 = 0
0 + -12a = 0 + -4
-12a = 0 + -4

Combine like terms: 0 + -4 = -4
-12a = -4

Divide each side by '-12'.
a = 0.3333333333

Simplifying
a = 0.3333333333

See similar equations:

| 20s=8 | | 9x+8=37 | | 2(y+8)=4(4y-6)+2y | | y=2sin^2(x) | | 9x^2+16=36 | | 2x+12=8x-12 | | 8a-3a=5 | | 0.2a=7 | | 11k-7k=16 | | 12x+13y=-465 | | 3(x+7)-6x=-(x-1)-8 | | 7v-6v=16 | | (3x-1)=(4x-2) | | 3(4b-7)=-2b+7 | | 3(x+7)-6x=-(x-1)-18 | | 2n-n=17 | | 3/8*-8-5 | | 25+12=-13 | | 3/8x-8-5 | | 20-15a+1b+6+4a-4b= | | Y^3=125/512 | | -92+66x=-10x^2+8x-8 | | ln(x)=1.624 | | 14(v+4)-2v=4(3v+3)-21 | | 4x+1+3x+2+2x+3+x-4=5(2x+2) | | =5(3+5) | | 7x^2+81=64 | | 5y^2+46y+105=0 | | 10+15x+3+2y+2x= | | 6y+4=12xfory | | 4x^(2/3)=108 | | Y=7(.98)x |

Equations solver categories